The Frequency of Bacterial Vaginosis among Pregnant Women and Its Link to Preterm Delivery - Mundada, Atulkumar (Journal of Biomedical and Pharmaceutical Research, 2019)
Background: Bacterial vaginosis (BV) is a common vaginal condition characterized by an imbalance in the vaginal microbiota. Its association with adverse pregnancy outcomes, particularly preterm delivery, has been the subject of ongoing research. This study aims to assess the prevalence of BV among pregnant women and examine its link to preterm delivery. The findings confirm that BV is prevalent among pregnant women and is significantly associated with an increased risk of preterm delivery. BV-positive women were more likely to experience preterm birth and require emergency Caesarean sections compared to those without BV. The data suggest that BV screening and treatment could potentially reduce the risk of preterm deliveries. Socioeconomic factors, such as lower socioeconomic status, were also found to be associated with higher BV prevalence. Bacterial vaginosis is a significant factor in predicting preterm delivery among pregnant women. Regular screening and timely treatment of BV are crucial for reducing the risk of preterm birth. Further research is needed to explore the mechanisms linking BV to preterm delivery and to develop effective prevention and management strategies, particularly in high-risk populations. Aim: The primary aim of this study is to evaluate the prevalence of bacterial vaginosis (BV) among pregnant women and to investigate its association with preterm delivery. Material and Method: A cross-sectional study was conducted in the Department of Obstetrics and Gynecology, involving 100 pregnant women. Written informed consent was obtained from all participants. At their first antenatal visit and during subsequent follow-ups, participants underwent a detailed history and physical examination. BV diagnosis was based on Amsel’s criteria, which includes assessing vaginal discharge characteristics, pH testing, and Gram staining of high vaginal swabs. The primary outcome was preterm delivery, defined as delivery before 37 weeks of gestation. Data on socio- demographic factors, previous pregnancy history, and delivery outcomes were collected and analyzed. Results: The data indicate that women in the lower socioeconomic class had a higher prevalence of BV and a higher rate of preterm births compared to women in the higher socioeconomic class. This may suggest a correlation between lower socioeconomic status and an increased risk of both BV and preterm birth. Further analysis would be needed to explore the factors contributing to these differences and to understand the potential underlying causes. The bacterial vaginosis is less commonly diagnosed in the very early stages of pregnancy and becomes more prevalent in the later stages. This could be due to several factors, including changes in vaginal flora or increased screening efforts as pregnancy progresses. BV-positive women had a higher incidence of preterm deliveries, while BV-negative women were more likely to have full-term vaginal deliveries. This suggests a potential association between BV and an increased risk of preterm birth. This underscores the potential impact of BV on pregnancy outcomes and the importance of monitoring and managing BV to improve delivery outcomes.